Fracture behaviors and crack propagation anisotropy in multi-ions modified bismuth titanate ferroelectrics - Xu, Qian; Xie, Shaoxiong; Zhao, Fuchao; Li, Lang; Zhang, Yangyue; Zhu, Jianguo; Wang, Qingyuan (Journal of Alloys and Compounds, 2024)
Bismuth titanate (BIT) is widely considered a promising lead-free piezoelectric material for advanced high-temperature applications. Despite significant advances in high-performance BIT ferroelectrics, there remains little understanding of mechanical properties including fracture failure and crack propagation behaviors, hindering the optimization of stability and reliability for next-generation high-temperature ferroelectrics. In this work, we investigated mechanical fracture and crack propagation behaviors of a type of high-performance bismuth titanate-based ceramic (Bi3.96Ce0.04Ti3–2xWxNbxO12, BCTWN) with different doping contents and electric poling states. High-resolution transmission electron microscopy (HRTEM) and electron backscatter diffraction (EBSD) results reveal that the BCTWN ceramics possess a single ferroelectric phase and exhibit layered crystal structures characterized by periodic fringe features. In addition, the striped domain structures are observed on the surface of plate-like grains. Mechanical measurements indicate that fracture behaviors of BCTWN ceramics are significantly affected by doping contents. The ceramics with the largest grain size present inferior microstructure with more defects, endowing the lowest bending strength and fracture toughness. For the samples with different poling states, strong anisotropy in crack propagation and fracture toughness is observed, attributed to the different domain switching mechanisms driven by local incompatible stress fields, which is experimentally validated by the intriguing evolutions of striped domain structures around crack tips. This work advances our understanding of the fracture and crack propagation mechanisms of BIT-based ceramics and provides insight into tailoring the mechanical behaviors through doping and poling strategies.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Anisotropy; Bismuth titanate-based ceramics; Crack propagation; Domain switching; Fracture behavior